Morphological characterization of the levator veli palatini muscle in children born with cleft palates - Lindman, R; Paulin, G; Stål, P S (The Cleft palate-craniofacial journal, 2001)
The aim of this study was to analyze, morphologically and biochemically, one of the soft palate muscles, the levator veli palatini (LVP), in children born with cleft palate. Biopsies were obtained from nine male and three female infants in connection with the early surgical repair of the hard and soft palate. Samples from five adult normal LVP muscles were used for comparison. The muscle morphology, fiber type and myosin heavy chain (MyHC) compositions, capillary supply, and content of muscle spindles were analyzed with different enzyme-histochemical, immunohistochemical, and biochemical techniques. Compared with the normal adult subjects, the LVP muscle from the infantile subjects with cleft had a smaller mean fiber diameter, a larger variability in fiber size and form, a higher proportion of type II fibers, a higher amount of fast MyHCs, and a lower density of capillaries. No muscle spindles were observed. Moreover, one-third of the biopsies from the infantile subjects with cleft LVP either lacked muscle tissue or contained only a small amount. The LVP muscle from children with cleft palate has a different morphology, compared with the normal adult muscle. The differences might be related to different stages in maturation of the muscles, changes in functional demands with growth and age, or a consequence of the cleft. The lack of contractile tissue in some of the cleft biopsies offers one possible explanation to a persistent postsurgical velopharyngeal insufficiency in some patients, despite a successful surgical repair.